Beyond ethanol: a techno‐economic analysis of an integrated corn biorefinery for the production of hydrocarbon fuels and chemicals. (16th December 2014) - Wang, Kaige; Ou, Longwen; Brown, Tristan; Brown, Robert C.
Abstract Dried distillers grains with solubles (DDGS) are potential feedstocks for the production of hydrocarbon fuels and chemicals from catalytic pyrolysis. This study evaluates the economic feasibility of a 2000‐metric‐ton‐corn‐per‐day integrated biorefinery with an add‐on facility processing corn DDGS to hydrocarbons. In addition to ethanol, the integrated facility would produce a wide range of hydrocarbons, including aromatics, olefins, and synthetic gasoline and diesel. The hydrocarbon products command a substantially higher market value than that of the pre‐processed DDGS: $109 million per year vs. $78 million per year. The add‐on DDGS conversion facility contributes an extra $152 million of capital investment compared with the stand‐alone corn ethanol production scenario. The operating costs for the integrated scenario are also higher than for the stand‐alone scenario, mainly due to increases in utilities, labor costs, and capital depreciation. The minimum fuel selling price (MFSP) for the integrated scenario is $2.27/gallon, which is comparable to the MFSP of $2.18/gallon for the stand‐alone scenario. Sensitivity analysis shows that the feedstock cost, hydrocarbon yield, and fixed capital investment have the greatest impacts on the MFSP. With the benefit of products diversity, the proposed integrated corn biorefinery may be competitive with conventional stand‐alone ethanol production. © 2014 Society of Chemical Industry and John Wiley & Sons, Ltd